PREVENTIVE MECHANISM AGAINST SIMPLE AND COOPERATIVE BLACK HOLE ATTACKS IN MULTI-HOP WIRELESS AD HOC NETWORKS - R, Praveenkumar; S, SivaSankaran (IJRDO -Journal of Computer Science Engineering, 2015)
This paper focuses on the issues related to the simple and cooperative black hole attacks in multihop wireless ad hoc networks. In multi-hop wireless ad hoc networks, nodes not in direct range rely on intermediate nodes to communicate. In order to preserve its limited resources or to launch a DoS attack, an intermediate node drops packets going through it instead to forward them to its succes- sor. In this paper, we deal with this misbehavior called black hole attack, and we propose an authenticated end-to-end acknowledgment based approach in order to check the correct forwarding of packets by intermediate nodes. Our approach detects the black hole conducted in simple or cooperative manner, the modification and the replay of messages attacks. Through simulation using OPNET simulator, we show the detection efficiency and evaluate the performance of our approach in both proactive and reactive routing based networks in terms of end-to-end delay and network load. Also, we compare the approach we propose with 2-hop ACK and the watchdog approaches in terms of detection ratio, delivery ratio and additional overhead.